Detection of cryptic species of Aspergillus with reduced susceptibility to antifungal agents in hospitals - Sabino, Raquel (2018)
Invasive aspergillosis is a fungal infection caused by Aspergillus spp. affecting mainly the immunocompromised. The mortality rate may reach 85%. Aspergillus identification should be based on molecular methods as there are species morphologically similar but distinct at the molecular level (cryptic species), with variable antifungal susceptibility profiles.